Prevalence and predictors of premarital sexual intercourse among young women in sub-Saharan Africa - Eugene Budu; Abdul-Aziz Seidu; Ebenezer Kwesi Armah-Ansah; James Boadu Frimpong; Richard Gyan Aboagye; Stephen Kofi Anin; John Elvis Hagan; Bright Opoku Ahinkorah (BMC, 2023)
Abstract Introduction Premarital sexual intercourse (PSI) without adequate information and/or appropriate application of the relevant knowledge about sex before marriage, potentially has adverse effects on the sexual and reproductive health outcomes of vulnerable young women in sub-Saharan Africa (SSA). This study sought to examine the prevalence and predictors of PSI among young women aged 15-24 in SSA. Methods Nationally representative cross-sectional data from 29 countries in SSA were extracted for the study. A weighted sample size of 87,924 never married young women was used to estimate the prevalence of PSI in each country. A multilevel binary logistic regression modelling approach was used to examine the predictors of PSI at p < 0.05. Results The prevalence of PSI among young women in SSA was 39.4%. Young women aged 20-24 (aOR = 4.49, 95% CI = 4.34, 4.65) and those who had secondary/higher educational level (aOR = 1.63, 95% CI = 1.54, 1.72) were more likely to engage in PSI compared to those aged 15-19 and those with no formal education. However, young women who belonged to the Islamic religion (aOR = 0.66, 95% CI = 0.56, 0.78); those who were working (aOR = 0.75, 95% CI = 0.73, 0.78); belonged to the richest wealth index (aOR = 0.55, 95% CI = 0.52, 0.58); were not exposed to radio at all (aOR = 0.90, 95% CI = 0.81, 0.99); were not exposed to television at all (aOR = 0.50, 95% CI = 0.46, 0.53); resided in rural areas (aOR = 0.73, 95% CI = 0.70, 0.76); and those who were living in the East African sub-region (aOR = 0.32, 95% CI = 0.29, 0.35) were less likely to engage in PSI compared to those who were traditionalist, unemployed, belonged to the poorest wealth index, exposed to radio frequently, exposed to television frequently, resided in urban areas, and lived in the Southern Africa sub-region, respectively. Conclusion Sub-regional variations in the prevalence of PSI exist amidst multiple risk factors among young women in SSA. Concerted efforts are required to empower young women financially, including education on sexual and reproductive health behaviors such as the detrimental effects of sexual experimentation and encouraging abstinence and/or condom use through regular youth-risk communication advocacy.